Environmental Analysis of the Ribeirão do Oratório Linear Park for Flood Mitigation, São Paulo – SP - Pinheiro, Leon Damico; Martins, Larissa Fernanda Vieira (Technical and Scientific Journal Green Cities, 2025)
Objective – This study aims to identify the contribution of the Ribeirão do Oratório Linear Park to flood control in the city of São Paulo, Brazil.Methodology – The study employed a comparative approach, collecting and tabulating precipitation data from the Ribeirão do Oratório watershed. Data covering a period of ten years before and ten years after the park’s implementation (2001–2021) were analyzed, using Microsoft Excel to generate charts. In addition, a spatial analysis of environmental characteristics, as well as land use and land cover in the area, was conducted using QGIS and Google Earth, based on data obtained from the Digital Map of the City of São Paulo (GeoSampa).Relevance – The research contributes to the debate on the effectiveness of nature-based solutions in mitigating urban problems such as flooding, as opposed to relying solely on traditional infrastructure works. Its academic relevance lies in presenting empirical evidence on the role of linear parks as tools for urban water management, integrating environmental, social, and public health dimensions.Results – The study did not provide conclusive evidence of the Ribeirão do Oratório Linear Park’s contribution to reducing floods, due to the lack of complete historical series and possible underreporting of events. However, it was observed that the detention basins (piscinões) in the region play an effective role in mitigating the water load of the stream.Theoretical and methodological contributions – This research contributes to the fields of urban planning and environmental management by presenting an integrated methodology that combines rainfall and georeferenced data to evaluate the performance of linear parks. It also reinforces the view of such spaces as multifunctional green infrastructures, extending beyond their recreational function.Social and environmental contributions – Socially, the Ribeirão do Oratório Linear Park fosters community integration with nature and helps prevent irregular settlements in risk areas, reducing the exposure of vulnerable populations to floods and diseases. Environmentally, it contributes to the preservation of riparian zones, local fauna and flora, and the improvement of the regional microclimate. Thus, this study highlights the importance of maintaining such areas as part of sustainable urban strategies.
Keywords: nature-based solutions; sustainable drainage; environmental management